2011
DOI: 10.1186/1471-2105-12-s4-s6
|View full text |Cite
|
Sign up to set email alerts
|

Deploying mutation impact text-mining software with the SADI Semantic Web Services framework

Abstract: BackgroundMutation impact extraction is an important task designed to harvest relevant annotations from scientific documents for reuse in multiple contexts. Our previous work on text mining for mutation impacts resulted in (i) the development of a GATE-based pipeline that mines texts for information about impacts of mutations on proteins, (ii) the population of this information into our OWL DL mutation impact ontology, and (iii) establishing an experimental semantic database for storing the results of text min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Because experimental findings are rarely reported to databases in a standardized form, metaresources, such as the Protein Mutant Database (PMD) (4) and Swiss-Prot/UniProt (5), manually curate publications to map variants to diseases. Natural language processing automates this mapping (6).…”
mentioning
confidence: 99%
“…Because experimental findings are rarely reported to databases in a standardized form, metaresources, such as the Protein Mutant Database (PMD) (4) and Swiss-Prot/UniProt (5), manually curate publications to map variants to diseases. Natural language processing automates this mapping (6).…”
mentioning
confidence: 99%
“…A general purpose solution can be adapted for use in a TM context by using TM resources if they are available, e.g. see a case study for SADI (89). Although general purpose workflow engines create an internal form of interoperability at the level of the process model, where all components within a workflow will work together, workflow engines from different providers cannot typically be expected to interact.…”
Section: Tools and Servicesmentioning
confidence: 99%
“…For more technical details on SADI and SHARE, the reader is referred to [13], and Bioinformatics- and Chemoinformatics-related case studies can be found in [15-18]. …”
Section: Introductionmentioning
confidence: 99%